PENGARUH PENGALAMAN KERJA,PRESTASI KERJA, PENDIDIKAN DAN PELATIHAN TERHADAP PENGEMBANGAN KARIR PERAWAT PNS RUMAH SAKIT UMUM DAERAH BADUNG MANGUSADA - Sumadewi, Ni Putu Asri; Suwandana, I Gusti Made (E-Jurnal Manajemen; Vol 6 No 8 (2017), 2017)
This research was conducted on nurse of civil servant of Badung Mangusada Regional General Hospital. The purpose of this study to determine the effect of work experience, job performance, education and training on career development at civil servant PNS Badung General Hospital Mangusada. Samples taken as much as 120 respondents, with probability sampling method, especially proportionate random sampling. The data was collected by distributing questionnaires using a 5-point likert scale to measure 19 statement items. The analysis technique used is multiple linear regression. The result of the analysis shows that work experience has a positive and significant effect on career development, work achievement has positive and significant impact on career development, education and training have positive and significant impact on career development, and also proven that work experience, work performance, education and Training has an effect on career development.